2019
DOI: 10.1186/s12889-019-7873-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of problematic mobile phone use and insufficient physical activity on depression symptoms: a college-based follow-up study

Abstract: BackgroundInsufficient physical activity (IPA) and mobile phone dependence are common coexisting behaviors among college students. However, the impact of the synergies between the two behaviors on depression has yet to be validated. Therefore, this study evaluated independent and interactive associations of problematic mobile phone use (PMPU) and IPA with depression symptoms and increased depressive symptoms among Chinese college students.MethodsIn total, 2134 college students participated in this follow-up st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 39 publications
3
29
2
1
Order By: Relevance
“…Nevertheless, the present study extends our knowledge of smartphone exposure towards self-reported symptoms' severity as perceived by the medical students in addition to the available evidence of smartphones affecting psychological health (13,15,24,50,51).…”
Section: Resultssupporting
confidence: 76%
“…Nevertheless, the present study extends our knowledge of smartphone exposure towards self-reported symptoms' severity as perceived by the medical students in addition to the available evidence of smartphones affecting psychological health (13,15,24,50,51).…”
Section: Resultssupporting
confidence: 76%
“…As we know, several studies showed the existence of the relationship between PA and suicidality. A study found the level of physical activity was associated with suicide attempt among 74,186 South Korean adolescents, and the result showed gender differences [19]. In our study, there was no signi cance gender differences for low PA students showed higher rates of suicidality.…”
Section: Discussioncontrasting
confidence: 58%
“…Multiple studies have shown that the rate of PMPU in adolescents is 6.3%-26% [14][15][16][17][18]. Thus far, the interaction effects between PA and PMPU on college students' mental health has been concerned [19]. A substantial body of research has demonstrated signi cant independent effects between low physical activity (LPA) and problematic mobile phone use (PMPU) on suicidality [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…As we know, several studies showed the existence of the relationship between PA and suicidality. A study found the level of physical activity was associated with suicide attempt among 74,186 South Korean adolescents, and the result showed a gender difference [19]. In our study, students reported low PA showed higher rates of suicidality, but there were no gender differences.…”
Section: Discussionsupporting
confidence: 40%
“…Multiple studies have shown that the rate of PMPU in adolescents is 6.3%-26% [14][15][16][17][18]. Thus far, the interaction effects between PA and PMPU on college students' mental health has been concerned [19]. A substantial body of researches has demonstrated signi cant independent effects between low physical activity (LPA) and problematic mobile phone use (PMPU) on suicidality [20][21][22].…”
Section: Introductionmentioning
confidence: 99%